Head and Neck Sarcomas Characteristics at Dr. Hasan Sadikin General Hospital for 5 Years (2017-2021) - Maya Sofa; Monty P. Soemitro; Maman Abdurahman; Yohana Azhar; Kiki A. Rizky (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Sarcoma is a malignant neoplasm originating from mesodermal tissue with an incidence rate of 1% of neoplasms throughout the body. Head and neck sarcoma requires more complex management and until now, reviews of this disease are still very rare. This study aimed to report the incidence and characteristics of head and neck sarcoma during 2017-2021 at Dr. Hasan Sadikin General Hospital, Universitas Padjadjaran, Bandung. Methods: Research data was taken from patient medical records through SIRS at Dr. Hasan Sadikin General Hospital during the 2017-2021 period according to the ICD10 of head and neck malignancies and histopathological data. Results: During 2017-2021, 15 cases of head and neck sarcoma were found, consisting of 9 cases (60%) rhabdomyosarcoma, 2 cases (13.3%) fibrosarcoma, and 1 case each (6.7%) synovial sarcoma, undifferentiated pleomorphic sarcoma, angiosarcoma and dermatofibrosarcoma protuberans. The neck and shoulder area are the most frequently affected site (40%), followed by the scalp (26.7%), maxilla (20%), and oral cavity (13.3%). The highest incidence rates were in female (60%) and children aged <17 years (46.7%). Conclusion: The incidence of head and neck sarcoma at Dr. Hasan Sadikin General Hospital Bandung is rare. The most frequent cases are rhabdomyosarcoma the most commonly affected areas are the neck and shoulders.